Preliminary Results of a Prospective Clinical and Radiological Study with Roentgen Stereophotogrammetric Analysis (RSA) after Implantation of a Posterior Dynamic Stabilization Device in the Lumbar Spine - Daentzer, Dorothea; Noll, Christine; Seehaus, Frank; Hurschler, Christof; Schwarze, Michael (International Journal of Orthopedics and Rehabilitation, 2022)
Introduction: Posterior dynamic stabilization (PDS) can be based on interspinous distraction devices (IDD). The goals of these implants are maintaining or restoring intervertebral range of motion (ROM) in a controlled fashion and avoiding a complete restriction of mobility. Clinical and radiological data with the Wallis® spacer as one type of IDD have been rarely reported. The goal of this study was to present clinical and radiological data including roentgen stereophotogrammetric analysis (RSA) after a short- to mid-term follow-up period. Patients and Methods: 10 patients were included in this prospective monocentric study and had PDS of the lumbar spine with an IDD (Wallis® spacer). Before and soon after operation and 3, 6, and 12 months later clinical and radiological evaluations were performed. Pain and disability were analyzed by use of visual analog scale for back and leg pain, Oswestry Disability Index, Roland-Morris Disability Questionnaire and Short-Form-36 Health Survey. The ROM of the operated levels and the total lumbar spine was determined by use of lateral functional x-ray images with calculation of the differences of the segmental and total lumbar spine angles in flexion and extension. Furthermore, RSA was used to measure the segmental ROM. Results: After a follow-up of 12 months, the results of the pain intensity and the disability and health related quality of life scores showed statistical significant improvement. The segmental angles of the operated levels demonstrated statistical significant reduction in ROM during the different follow-up examinations. The discrepancy of the conventionally determined segmental angles and the data measured by RSA were low with a mean of 1.77°. The mean total lumbar spine angles did not change statistically significantly during the postoperative controls. Conclusions: According to the radiological results of this study, the used implant leads to a posterior dynamic stabilization. The clinical findings are promising, but they are to be interpreted with caution because of the small number of patients and the lack of a control group.